Lean body mass as an independent determinant of dose‐limiting toxicity and neuropathy in patients with colon cancer treated with FOLFOX regimens. (27th January 2016) - Ali, Raafi; Baracos, Vickie E.; Sawyer, Michael B.; Bianchi, Laurent; Roberts, Sarah; Assenat, Eric; Mollevi, Caroline; Senesse, Pierre
Abstract: Evidence suggests that lean body mass (LBM) may be useful to normalize chemotherapy doses. Data from one prospective and one retrospective study were used to determine if the highest doses of oxaliplatin/kg LBM within FOLFOX regimens would be associated with dose‐limiting toxicity (DLT) in colon cancer patients. Toxicity over four cycles was graded according to NCI Common Toxicity Criteria V2 or V3 (Common Terminology Criteria for Adverse Events, National Cancer Institute, Bethesda, MD). Muscle tissue was measured by computerized tomography (CT) and used to evaluate the LBM compartment of the whole body. In prospective randomized clinical trials conducted in France ( n  =   58), for patients given FOLFOX‐based regimens according to body surface area, values of oxaliplatin/kg LBM were highly variable, ranging from 2.55 to 6.6 mg/kg LBM. A cut point of 3.09 mg oxaliplatin/kg LBM for developing toxicity was determined by Receiver Operating Characteristic (ROC) analysis, below this value 0/17 (0.0%) of patients experienced DLT; in contrast above this value 18/41 (44.0%) of patients were dose reduced or had treatment terminated owing to toxicity (≥Grade 3 or neuropathy ≥Grade 2); for 9/41 the DLT was sensory neuropathy. These findings were validated in an independent cohort of colon cancer patients ( n  =   80) receiving FOLFOX regimens as part of standard care, in Canada. Low LBM is a significant predictor of toxicity and neuropathy in patients administered FOLFOX‐based regimens using conventional body surface area (BSA) dosing. Abstract : Depleted lean body mass is a strong predictor of the risk of dose‐limiting sensory neuropathy and overall toxicity in patients treated with FOLFOX regimens. Lean tissue can be quantified using CT images and this minimally invasive, fast, and cost effective.